ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN BELI (Studi pada Konsumen Kosmetik di Bangkalan) - Fathor A. S (Universitas Trunojoyo Madura, 2011)
The purpose of this study was to determine whether cultural, social, personal, psychological have significant effects simultaneously and partially on consumer behavior in the decision to buy cosmetics in Bangkalan. Primary data was collected by spreading quesioner and interviews, while secondary data obtained from reports in Bangkalan minimarket. Population is female cosmetics users who shop at the minimarket in Bangkalan. Sampling technique used was purposive sampling. Number of sample size 50. Cultural factors independent variables (X1), social (X2), personal (X3), psychology (X4) and the dependent variable is the purchase decision (Y) and measured with a Likert scale. Analysis technique used is descriptive analysis and multiple linear regression. The results of the analysis found that the independent variables simultaneously cultural factors (X1), social (X2), personal (X3), psychology (X4) variables influencing the purchase decision (Y), no significant influence of cultural factors on consumer behavior in the decision to buy cosmetics, social factors significantly affect consumer behavior in the decision to buy cosmetics, personal factors significantly influence consumer behavior in purchasing decisions of cosmetic and psychological factors have a significant impact on consumer behavior in the decision to buy cosmetics.